Nuevos registros de plantas hospederas y distribución geográfica de Melanagromyza floris Spencer, M. tomaterae Steyskal, M. viridis (Frost) y Ophiomyia lantanae (Froggatt) (Diptera: Agromyzidae) en México - Palacios-Torres, Rogelio Enrique; Valdez-Carrasco, Jorge Manuel; Étienne, Jean; Vega-Muñoz, Ricardo; Marín-Sánchez, José; Castañeda-Vildozola, Álvaro; Nava-Díaz, Cristian (Instituto de Ecología, A.C., 2010)
The objective of this study was to document new host plants and the geographical distributions of Melanagromyza floris Spencer, M. tomaterae Steyskal, M. viridis (Frost) and Ophiomyia lantanae (Froggatt). The study was carried out from August 2007 to August 2008. Puparia of these flies were collected on Tithonia sp. in Tonatico (state of Mexico); Physalis nicandroides Schltd in Atotonilco el Grande (state of Hidalgo); Tagetes erecta L. and Lantana camara L. in Huautla (state of Hidalgo) and Lantana camara L. in San Joaquin, state of Queretaro. Both flies and host plants were identified. T. erecta is a new host record for M. floris whereas P. nicandroides is a new host record for M. tomaterae. The flies M. floris and M. tomaterae are the first reports for these species in the state of Hidalgo. M. viridis is recorded from the southern part of the state of Mexico. Finally, O. lantanae is registered in two states: Hidalgo and Queretaro.